Construction education in Australia : a review of learning and teaching challenges and opportunities. - Williams, Anthony; Sher, William; Simmons, Catharine; Dosen, Annemarie; Pitt, Brendan (Australian Learning & Teaching Council, 2010)
This report documents the first comprehensive study of university construction education in Australia. It provides a detailed overview and analysis of the issues facing the providers of Construction (construction management, quantity and building surveying) degrees in Australia. The report achieves the following: showcases the disciplines to all stakeholders including universities, industry and community and makes clear that the disciplines of construction management, quantity surveying and building surveying (collectively referred to hereafter as Construction disciplines) deserve greater recognition for their contributions to stakeholders' interests; raises self-awareness of the disciplines' characteristics, issues, opportunities and boundaries; identifies teaching and learning challenges and opportunities for Construction providers and highlights directions for future changes and developments; provides a foundation for future research into Construction education across the region; identifies areas for future research and changes required for the disciplines. [p.9, ed]